2009
DOI: 10.1029/2008jb006106
|View full text |Cite
|
Sign up to set email alerts
|

Integrated archeomagnetic and micro–Raman spectroscopy study of pre‐Columbian ceramics from the Mesoamerican formative village of Cuanalan, Teotihuacan Valley, Mexico

Abstract: [1] We report a detailed archeomagnetic and micro-Raman spectroscopy investigation on pre-Columbian pottery fragments from Cuanalan (a formative village in the valley of Teotihuacan, central Mexico). Available radiocarbon ages range from 2320 ± 80 to 2060 ± 90 B.P. Continuous low-field susceptibility versus temperature curves performed in air indicate Ti-poor titanomagnetites as magnetization carriers. Few samples, however, show two ferrimagnetic phases with Curie temperatures compatible with both Ti-poor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…9) is the intensity obtained at about 200 B.C. (Rodriguez-Ceja et al, 2009) which should be confirmed by further investigations. …”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…9) is the intensity obtained at about 200 B.C. (Rodriguez-Ceja et al, 2009) which should be confirmed by further investigations. …”
Section: Resultssupporting
confidence: 65%
“…The mean archeointensity obtained in the present study agrees reasonably well with the predicted absolute intensities retrieved from CALS7K global model. Other available Mesoamerican data however differ from this model (Rodriguez-Ceja et al, 2009). It should be noted that many archeoinintensity determinations used in Korte and Constable's (2005) model are not corrected for cooling rate and remanence (TRM) anisotropy.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations